2011
DOI: 10.1107/s1600536811034994
|View full text |Cite
|
Sign up to set email alerts
|

Redetermination of (E)-3-(anthracen-9-yl)-1-(2-hydroxyphenyl)prop-2-en-1-one

Abstract: The redetermined structure of title chalcone derivative, C23H16O2, corrects errors in the title, scheme and synthesis in the previous report of the same structure [Jasinski et al. (2011 ▶). Acta Cryst. E67, o795]. There are two independent mol­ecules in the asymmetric unit with slight differences in bond lengths and angles. The dihedral angle between the benzene ring and the anthracene ring system is 73.30 (4)° in one mol­ecule and 73.18 (4)° in the other. Both mol­ecules feature an intra­molecular O—H⋯O hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…search of the Cambridge Structural Database (Version 5.40, last update February 2019;Groom et al, 2016) revealed six closely related fused-ring chalcones, namely, trans-3-(9-anthryl)-1-(4-methoxyphenyl)prop-2-en-1-one (refcode EMULIT; Zhang et al, 2016), 3-(anthracen-9-yl)-1-(4-chlorophenyl)prop-2-en-1-one (JAHPUG; Yu et al, 2017), (E)-3-(anthracen-9-yl)-1-(4-bromophenyl)prop-2-en-1-one (POP-BAY;Suwunwong et al, 2009), (Z)-3-(anthracen-9-yl)-1-(2ethoxyphenyl)prop-2-en-1-one (KABHUS; Joothamongkhon et al, 2010), (E)-3-(anthracen-9-yl)-1-(2-hydroxyphenyl)prop-2-en-1-one (UNUDUD;Jasinski et al, 2011; UNUDUD01;Chantrapromma et al, 2011), (E)-3-(anthracen-9-yl)-1-(2bromophenyl)prop-2-en-1-one (WAFGOB;Fun et al, 2010).…”
mentioning
confidence: 99%
“…search of the Cambridge Structural Database (Version 5.40, last update February 2019;Groom et al, 2016) revealed six closely related fused-ring chalcones, namely, trans-3-(9-anthryl)-1-(4-methoxyphenyl)prop-2-en-1-one (refcode EMULIT; Zhang et al, 2016), 3-(anthracen-9-yl)-1-(4-chlorophenyl)prop-2-en-1-one (JAHPUG; Yu et al, 2017), (E)-3-(anthracen-9-yl)-1-(4-bromophenyl)prop-2-en-1-one (POP-BAY;Suwunwong et al, 2009), (Z)-3-(anthracen-9-yl)-1-(2ethoxyphenyl)prop-2-en-1-one (KABHUS; Joothamongkhon et al, 2010), (E)-3-(anthracen-9-yl)-1-(2-hydroxyphenyl)prop-2-en-1-one (UNUDUD;Jasinski et al, 2011; UNUDUD01;Chantrapromma et al, 2011), (E)-3-(anthracen-9-yl)-1-(2bromophenyl)prop-2-en-1-one (WAFGOB;Fun et al, 2010).…”
mentioning
confidence: 99%